Leadership styles of school principals: a comparison among principals of governmental schools, private language schools and international schools in Egypt. - Habashy, Maged Makram (AUC Knowledge Fountain, 2016)
School leadership is an important aspect of the educational system. It has been the focus of much research because it affects many other factors in the educational process. Links are found in the literature between school leadership and other variables related to students’ academic achievement and teachers’ performance and teacher retention. The aim of the current study was to compare the leadership styles of school principals of three types of schools in the Egyptian context and to link their leadership style to their job responsibilities. A convenient sample (N=29) of 10 governmental schools’ principals, 9 private language schools’ principals, and 10 international schools’ principals comprised the participants in this study. Two instruments were used; the first was Multifactor Leadership Questionnaire (MLQ) to measure the school principals’ leadership styles and the second was an abridged form of The OECD (TALIS) Principal Questionnaire to determine the school principals job responsibilities. Statistical Package for the Social Sciences SPSS® v.19 was used for the quantitative data analysis. The major findings of the current study were that the transformational leadership style was the predominant style for all school principals in all three school types. Principals of governmental schools scored higher than principals of private language schools and international schools. Principals of governmental schools were not involved in any item of the school resources related to teachers and budgeting. Future studies could target the effect of different leadership styles on other variables such as students’ academic achievement and teacher performance in the Egyptian context.